Developing effective chronic disease interventions in Africa: insights from Ghana and Cameroon - Boynton Petra; de-Graft Aikins Ama; Atanga Lem L (BMC, 2010)
Abstract Background Africa faces an urgent but 'neglected epidemic' of chronic disease. In some countries stroke, hypertension, diabetes and cancers cause a greater number of adult medical admissions and deaths compared to communicable diseases such as HIV/AIDS or tuberculosis. Experts propose a three-pronged solution consisting of epidemiological surveillance, primary prevention and secondary prevention. In addition, interventions must be implemented through 'multifaceted multi-institutional' strategies that make efficient use of limited economic and human resources. Epidemiological surveillance has been prioritised over primary and secondary prevention. We discuss the challenge of developing effective primary and secondary prevention to tackle Africa's chronic disease epidemic through in-depth case studies of Ghanaian and Cameroonian responses. Methods A review of chronic disease research, interventions and policy in Ghana and Cameroon instructed by an applied psychology conceptual framework. Data included published research and grey literature, health policy initiatives and reports, and available information on lay community responses to chronic diseases. Results There are fundamental differences between Ghana and Cameroon in terms of 'multi-institutional and multi-faceted responses' to chronic diseases. Ghana does not have a chronic disease policy but has a national health insurance policy that covers drug treatment of some chronic diseases, a culture of patient advocacy for a broad range of chronic conditions and mass media involvement in chronic disease education. Cameroon has a policy on diabetes and hypertension, has established diabetes clinics across the country and provided training to health workers to improve treatment and education, but lacks community and media engagement. In both countries churches provide public education on major chronic diseases. Neither country has conducted systematic evaluation of the impact of interventions on health outcomes and cost-effectiveness. Conclusions Both Ghana and Cameroon require a comprehensive and integrative approach to chronic disease intervention that combines structural, community and individual strategies. We outline research and practice gaps and best practice models within and outside Africa that can instruct the development of future interventions.